Cellular and Microenvironmental Functions of SNHG lncRNAs in Tumor Immune Remodeling - Tareq Nayef Alramadneh; Afaq Mahdi Ali; Fatima Muhammad Yunus; Pareshkumar N. Patel; K. Jamuna; Vandana Tripathi; Priya Priyadarshini Nayak; Navin Kumar Tailor (Tissue and Cell, 2026)

Uncovering land subsidence recovery in the Jakarta metropolitan region, Indonesia, from satellite remote sensing - Muhammad Yunus; Ruey-Juin Rau; Sung-Ping Chang; Reyhan Azeriansyah; Chih-Heng Lu (Remote Sensing Applications: Society and Environment, 2026)

Policy forum: Between incorporation and reappropriation – The unresolved dilemma of oil palm in Indonesia's forest zones - Muhammad Alif K. Sahide; Fatwa Faturachmat; Abdurahman Abdullah; Muh Ichwan Kadir; Ahsan Yunus; Ahmad Maryudi (Forest Policy and Economics, 2026)

Contamination of mercury in paddy soils from gold mining in Tasikmalaya regency, West Java, Indonesia: spatial distribution, ecological and human health risk assessment - Willy Cahya Nugraha; Fadhlan Khusyairi Tarigan; Muhammad Haikal Razi; Dadan Sumiarsa; Yunus Winoto (Environmental Geochemistry and Health, 2026)

First report of Steneotarsonemus spinki Smiley (Trombidiformes: Tarsonemidae) infesting greenhouse-grown rice (Oryza sativa L. ssp. indica cv. MR 297) in Malaysia - Noriha Mat Amin; Munirah Tharek; Suhana Yusof; Amin Asyraf Tamizi; Maisarah Mohamad Saad; Siti Akhtar Mohshim; Azlinda Erny Yunus; Muhammad Zamharir Ahmad (Australasian Plant Pathology, 2026)

A toolkit for the assessment of training needs and gaps of the national Veterinary Services in field epidemiology - Imadidden Musallam; Julio Pinto; Ravi Bandara Dissanayake; Muhammad Usman Zaheer; Zaidoun Hijazeen; Wafa’a Ramadneh; Iqbal Qatananni; Esam Hawa; Majed Hawaowsheh; Ehab Abu-Basha; Aida binti Muhid; Jamaliah binti Senawi; et al. (The Veterinary Journal, 2026)

Probiotic-based mycotoxin detoxification in poultry feed: mechanisms, efficacy, challenges, and future directions for sustainable production - Noor Muhammad; Iram Liaqat; Sajida Naseem; Fakhar-un Nisa Yunus; Abid Ali (Archives of Microbiology, 2026)

Allelopathic effects of rice husk on goosegrass (Eleusine indica) and lettuce (Lactuca sativa) - Nurul Solehah Binti Samsudin; Siti Aisyah Mohammad Taupik; Chia Poh-Wai; Dilipkumar Masilamany; Muhammad Ammar Yunus; Chuah Tse-Seng (South African Journal of Botany, 2026)

A PAGER framework-enhanced bibliometric analysis of global nuclear desalination research trends (2005–2024) - Nanang Apriandi; Khoiri Rozi; Mukhsinun Hadi Kusuma; Berkah Fajar Tamtomo Kiono; Rani Raharjanti; Yoyok Dwi Setyo Pambudi; Muhammad Yunus; Sofia Loren Butarbutar; Giarno; Sumantri Hatmoko; Afifa Pramesywari (Desalination, 2025)

Retraction Note: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2025)

Spatial distribution of heavy metal abundance at distance gradients of roadside agricultural soil from the busiest highway in Bangladesh: A multi-index integration approach - Md. Saydul Islam; Md. Nur-E-Alam; Muhammad Anwar Iqbal; Md. Badiuzzaman Khan; Shamim Al Mamun; Md. Yunus Miah; Md. Rasheduzzaman; S. Appalasamy; Mohammed Abdus Salam (Environmental Research, 2024)

Poly-(ionic liquid) coated with magnetic nanoparticles for micro solid phase extraction of polycyclic aromatic hydrocarbons in food samples - Faizah Muhammad Yunus; Yatimah Alias; Noorfatimah Yahya; Nur Nadhirah Mohamad Zain; Muggundha Raoov (Food Additives & Contaminants: Part A, 2024)

Potential application of 2D nano-layered MXene in analysing and remediating endocrine disruptor compounds and heavy metals in water - Muhammad Nur’ Hafiz Rozaini; Kuan Shiong Khoo; Muhammad Amirul Aizat Mohd Abdah; Baranitharan Ethiraj; Mohammad Mahtab Alam; Aliya Fathima Anwar; Normawati M. Yunus; Chin Seng Liew; Jun Wei Lim; Chii-Dong Ho; Woei-Yenn Tong (Environmental Geochemistry and Health, 2024)

Adaptation of coastal defence structure as a mechanism to alleviate coastal erosion in monsoon dominated coast of Peninsular Malaysia - Wan Shiao Dong; Effi Helmy Ariffin; Cherdvong Saengsupavanich; Muhammad Aizat Mohd Rashid; Mohamad Hakim Mohd Shukri; Muhammad Zahir Ramli; Mohd Fuad Miskon; Muhammad Hafeez Jeofry; Kamaruzzaman Yunus; Nor Hisham M. Ghazali; Md Nasir Md Noh (Journal of Environmental Management, 2023)

An insight into the mechanisms of action of selected bioactive compounds against epigenetic targets of prostate cancer: implications on histones modifications - Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Abdurrahman Pharmacy Yusuf; Yunus Aisha Lawal; Shehu Aisha Jibril; Hussaini Nuraddeen; Musa Mubarak Ibrahim; Idris Zubairu Sadiq; Murtala Bello Abubakar; Ibrahim Malami; Ibrahim Babangida Abubakar; Aliyu Muhammad (In Silico Pharmacology, 2023)

Southern South China Sea Dynamics: Sea Level Change from Coupled Model Intercomparison Project Phase 6 (CMIP6) in the 21st Century - Noah Irfan Azran; Hafeez Jeofry; Jing Xiang Chung; Liew Juneng; Syamir Alihan Showkat Ali; Alex Griffiths; Muhammad Zahir Ramli; Effi Helmy Ariffin; Mohd Fuad Miskon; Juliana Mohamed; Kamaruzzaman Yunus; Mohd Fadzil Akhir (Journal of Marine Science and Engineering, 2023)
Sea level rise will significantly impact coastal areas around the world. As a coastal country, Malaysia’s rising sea levels are a significant concern because they would affect 70% of its population. The study of sea level rise is important in order to implement effective mitigation and adaptation strategies. This study investigates the performance of CMIP6 Global Climate Models (GCMs) in simulating sea level rise in the Malaysian seas using various statistical methods. The models’ performances were evaluated by comparing historic CMIP6 GCM runs from 1993 to 2010 with sea level measurements from the satellite altimetry AVISO+ using the Taylor diagram. The SCS (SCSPM and SCSEM) had a higher sea level range and trend in both selected areas than the SM and SS. With 1.5 °C warmings, the multi-model ensemble means predicted that the SCS would rise by 16 mm near the Peninsular, with sea levels increasing by 0.908 m at a rate of 1.5 mm/year, and by 14.5 mm near East Malaysia, with sea levels increasing by 0.895 m at a rate of 1.1 mm/year. In contrast, 2.0 °C warmings project that SCSPM and SCSEM would cause sea levels to rise by 20.2 mm and 21.5 mm, respectively, at a rate of 0.6 mm/year and 0.7 mm/year. This information will provide an insight into Malaysian sea levels between now and the end of the twenty-first century, which will be beneficial for government agencies, academics, and relevant stakeholders.

Carbonated ground granulated blast furnace slag stabilising brown kaolin - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Ahmad Safuan A. Rashid; Suksun Horpibulsuk (Environmental Science and Pollution Research, 2021)

Refinement of gravimetric geoid model by incorporating terrestrial, marine, and airborne gravity using KTH method - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Mohd Yunus Mohd Yusoff; Ramazan Alpay Abbak; Mohammad Hanif Hamden (Arabian Journal of Geosciences, 2021)

Polymerase chain reaction cycle threshold value as prerequisite for reporting of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection - Hafizuddin Awang; Fathul Hakim Hamzah; Mohd Hanief Ahmad; Muhammad Faris Mahmood; Azmani Wahab; Kasemani Embong; Nor Azimi Yunus (Infectious Diseases, 2021)

RETRACTED ARTICLE: Evaluation of toxicity potential of cobalt in wheat irrigated with wastewater: health risk implications for public - Fu Chen; Zafar Iqbal Khan; Asma Zafar; Jing Ma; Muhammad Nadeem; Kafeel Ahmad; Shehzadi Mahpara; Kinza Wajid; Humayun Bashir; Mudasra Munir; Ifra Saleem Malik; Asma Ashfaq; et al. (Environmental Science and Pollution Research, 2021)

A case–control study of determinants for COVID-19 infection based on contact tracing in Dungun district, Terengganu state of Malaysia - Hafizuddin Awang; Effah Leiylena Yaacob; Sharifah Nadira Syed Aluawi; Muhammad Faris Mahmood; Fathul Hakim Hamzah; Azmani Wahab; Norafidah Abdul Rashid; Rosmaliza Razali; Goh Soo Ning; Kasemani Embong; Nor Azimi Yunus (Infectious Diseases, 2021)

Correction to: Ground improvement and its role in carbon dioxide reduction: a review - Ahmed Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

Ground improvement and its role in carbon dioxide reduction: a review - Mohammed Awad Mohammed; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi; Dayang Zulaika Abang Hasbollah; Ahmad Safuan A Rashid (Environmental Science and Pollution Research, 2021)

Evaluating the toxicity of polyurethane during marine clay stabilisation - Samaila Saleh; Kamarudin Ahmad; Nor Zurairahetty Mohd Yunus; Muhammad Azril Hezmi (Environmental Science and Pollution Research, 2020)

Litter decay in rangeland sites with varying history of human disturbance: a study with Hazargangi Chiltan mountain - Imran Khan; Shamim Gul; Sarfraz Ahmad; Gul Bano Rehman; Agha Waqar Yunus; Iram Gul; Imran Ali; Ali Akbar; Muhammad Islam (Journal of Mountain Science, 2020)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Metal accumulation in Raphanus sativus and Brassica rapa: an assessment of potential health risk for inhabitants in Punjab, Pakistan - Kafeel Ahmad; Asma Ashfaq; Zafar Iqbal Khan; Humayun Bashir; Muhammad Sohail; Naunain Mehmood; Yunus Dogan (Environmental Science and Pollution Research, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Historical and projected changes in the Southern Hemisphere Sub-tropical Jet during winter from the CMIP5 models - Sheeba Nettukandy Chenoli; Muhammad Yunus Ahmad Mazuki; John Turner; Azizan Abu Samah (Climate Dynamics, 2017)

Modelling the kinetics of hexavalent molybdenum (Mo6+) reduction by the Serratia sp. strain MIE2 in batch culture - Mohd Izuan Effendi Halmi; Siti Rozaimah Sheikh Abdullah; Wan Lutfi Wan Johari; Mohd Shukuri Muhammad Ali; Noor Azmi Shaharuddin; Ariff Khalid; Mohd Yunus Shukor (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Antiproliferative potential of sarcophine and its semisynthetic sulfur-containing derivatives against human mammary carcinoma cell lines - Jamal M. Arif; Swapnali S. Sawant; Khalid A. El Sayed; Muhammad Kunhi; Manogaran P. Subramanian; Yunus M. Siddiqui; Diaa T. A. Youssef; Khalid Al-Hussain; Mohammed N. Al-Ahdal; Fahad Al-Khodairy (Journal of Natural Medicines, 2007)